2022
DOI: 10.3390/microorganisms10081584
|View full text |Cite
|
Sign up to set email alerts
|

Assays for Identification and Differentiation of Brucella Species: A Review

Abstract: Brucellosis is one of the most important and widespread bacterial zoonoses worldwide. Cases are reported annually across the range of known infectious species of the genus Brucella. Globally, Brucella melitensis, primarily hosted by domestic sheep and goats, affects large proportions of livestock herds, and frequently spills over into humans. While some species, such as Brucella abortus, are well controlled in livestock in areas of North America, the Greater Yellowstone Ecosystem supports the species in native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 102 publications
0
18
0
1
Order By: Relevance
“…Вместе с тем сочетание лимфаденопатии, гепатоспленомегалии, длительной лихорадки, артралгий позволяли предположить у больного течение бруцеллёза и назначить специфическое обследование. Существуют объективные трудности лабораторной диагностики бруцеллёза [10,11], однако в течение полугода пациенту не были назначены даже рутинные анализы для диагностики данного заболевания. Более внимательные сбор и оценка данных эпидемиологического анамнеза (пациент прибыл из эндемичного по бруцеллёзу региона [12], пил сырое козье молоко) позволили бы значительно ускорить постановку диагноза и раньше назначить адекватную терапию.…”
Section: Discussionunclassified
“…Вместе с тем сочетание лимфаденопатии, гепатоспленомегалии, длительной лихорадки, артралгий позволяли предположить у больного течение бруцеллёза и назначить специфическое обследование. Существуют объективные трудности лабораторной диагностики бруцеллёза [10,11], однако в течение полугода пациенту не были назначены даже рутинные анализы для диагностики данного заболевания. Более внимательные сбор и оценка данных эпидемиологического анамнеза (пациент прибыл из эндемичного по бруцеллёзу региона [12], пил сырое козье молоко) позволили бы значительно ускорить постановку диагноза и раньше назначить адекватную терапию.…”
Section: Discussionunclassified
“…23 Several other molecular studies suggested the close relationship among different biovars and the difficulty in differentiating B. canis from B. suis. [24][25][26][27] Recently, a new multiplex PCR assay accurately identified B. suis at the biovar level and differentiated B. suis from B. canis. 28 Whole-genome analysis indicated that B. canis had arisen directly from B. suis based on a high similarity between the genomes of these two species.…”
Section: Discussionmentioning
confidence: 99%
“…Roughly 120 species of marine animals either exclusively inhabit maritime environments or are heavily reliant on marine resources for survival. These animals include pinnipeds (true seals, eared seals, and walruses) [49]; cetaceans (which contain two suborders: Mysticeti (baleen whales) [50] and Odontoceti (toothed whales, which includes dolphins and porpoises) [51]; polar bear (Ursusmaritimus) [52]; sirenians (manatees and dugong) [53]; and several species of otters [10].…”
Section: Marine Mammal Brucellosismentioning
confidence: 99%
“…Even though brucellosis seldom poses a threat to human life, it is widely seen as a burden for the economy and public health, notably in the Middle East, Mediterranean region, North and East Africa, Southern and Central Asia, India, Central, and South America. According to the European Food Safety Authority, brucellosis incidence rates in developed countries range from 0.3 cases per million per year to over 1000 cases per million in endemic regions [9,10].…”
Section: Introductionmentioning
confidence: 99%